The Effect of E-Commerce in Reducing the Actual Unemployment Rate among Saudi Youth - Al-Hrbi, Waleed Hasen; Al-Shah, Ahmed Abdul-Wakeel (Journal of Economic, Administrative and Legal Sciences, 2021)
The study aimed to determine the impact of E-commerce in reducing the unemployment rate among Saudi youth in the Kingdom of Saudi Arabia. The study deals with many important concepts, which are E-commerce, the unemployment rate, and the important role that e-commerce can play in contributing to reducing the actual unemployment rates among Saudi youth in the Kingdom of Saudi Arabia. The study problem is determined in the following question: What is the effect of e-commerce in reducing the actual unemployment rate among Saudi youth? The study adopted the analytical descriptive approach. The study sample consisted of (142) e-store owners, workers in electronic stores, unemployed and consumers in the Kingdom of Saudi Arabia. Their data were collected through a questionnaire. The study found the following results: The infrastructure in the Kingdom is well prepared through the existence of a special system for e-commerce and the ease of opening the e-store, and that there is ambiguity among Saudi youth regarding e-commerce, perhaps for lack of adequate awareness, but e-commerce is generally acceptable when Saudi youth, and the work of women in electronic stores is very appropriate due to the nature of their family conditions, and the skills and potential of the Saudi youth are compatible with the job requirements in electronic stores. The researchers recommended that the necessary support be provided to Saudi youth by the concerned authorities such as the Ministry of Commerce and the Ministry of Investment to work in the e-commerce sector and find appropriate solutions to the problems they face, and the Saudi youth should follow the correct methods when thinking about working in the field of e-commerce, and pay attention to supporting women in particular. To work in the e-commerce sector, especially since more female unemployed than male unemployed.
Keywords: e-commerce; unemployment rate; unemployment e-market; online sales; online business; online stores